Effects of Vitamin E Supplementation on Reducing Chronic Hemolysis in Glucose 6 Phosphate Dehydrogenase (G6PD) Deficiency - Sultana, Nayma; Begum, Noorzahan; Begum, Shelima; Ferdousi, Sultana; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2011)
Background: Vitamin E works within the cell membrane as an antioxidant and may prevent destruction of RBC in G6PD deficient hemolytic anemia, which can be reflected by changes in peripheral blood film. Objective: To observe the role of vitamin E supplementation on restoring normal cell types in peripheral blood film in order to evaluate the role of this antioxidant vitamin in reducing chronic hemolysis in G6PD deficient patients. Method: Total 102 subjects, age range from 5-40 years of both sexes were included in the study. Among them 68 were G6PD enzyme deficient patients, of whom 34 were in non-supplemented group (Group B) and 34 were in supplemented group (Group C). Both group B and C were divided into Group B1 and C1 (on day 1 ) and also into B2 and C2 (on day 60) respectively. Supplemented group received vitamin E supplementation for 60 consecutive days (800 IU/day for adult and 400 IU/day for children in a divided dose i,e. 4 times daily). Age and sex matched 34 apparently healthy subjects with normal G6PD level (Group A) were also taken to observe baseline data. Determination of Erythrocyte G6PD level and preparation of peripheral blood film were done on day 1 for all groups and also on day 60 in deficient groups. Results: Percentage of subjects with presence of some abnormal red cells in peripheral blood film was significantly higher in patients of hemolytic anemia with G6PD deficiency in comparison to that of healthy control. After supplementation with vitamin E (i,e. on day-60) this percentage was significantly decreased towards those of healthy control in their supplemented group in comparison to that of pre-supplemented (day-1) and nonsupplemented groups. Conclusion: Some abnormal red cells may be found in peripheral blood film of G6PD deficient patients, improvement of which occur following vitamin E supplementation, and thereby indicates role of this antioxidant vitamin in reducing the rate of hemolysis. Key words: G6PD deficiency; Peripheral blood film; Vitamin E DOI: http://dx.doi.org/10.3329/jbsp.v6i1.8088 J Bangladesh Soc Physiol. 2011 June; 6(1): 70-76